2021
DOI: 10.1038/s10038-021-00942-w
|View full text |Cite
|
Sign up to set email alerts
|

From HDLS to BANDDOS: fast-expanding phenotypic spectrum of disorders caused by mutations in CSF1R

Abstract: Colony-stimulating factor 1 receptor (CSF1R) plays key roles in the development and function of the cells in the monocyte/ macrophage lineage, including microglia and osteoclasts. It is well known that mono-allelic mutations of CSF1R cause hereditary diffuse leukoencephalopathy with spheroids (HDLS, OMIM # 221820), an adult-onset progressive neurodegenerative disorder. Recently, a more severe phenotypic spectrum has been identified in individuals with bi-allelic mutations of CSF1R. In addition to leukoencephal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Neither the microgliosis phenotype nor changes in microglia-specific gene expression was replicated in Csf1r +/− rats ( Patkar et al, 2021a ). Similarly, there is no reported evidence of neuropathology in aged obligate carriers of recessive CSF1R loss-of-function alleles in humans ( Guo et al, 2019 ; Guo and Ikegawa, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neither the microgliosis phenotype nor changes in microglia-specific gene expression was replicated in Csf1r +/− rats ( Patkar et al, 2021a ). Similarly, there is no reported evidence of neuropathology in aged obligate carriers of recessive CSF1R loss-of-function alleles in humans ( Guo et al, 2019 ; Guo and Ikegawa, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, Rademakers et al (2011) reported heterozygous amino acid substitutions in the tyrosine kinase domain of CSF1R in patients with autosomal dominant adult-onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP), now also called CSF1R-related leukoencephalopathy (CRL) ( Chitu et al, 2021 ). Since then, more than 100 different disease-associated CSF1R coding mutations have been identified ( Chitu et al, 2021 ; Guo and Ikegawa, 2021 ; Konno et al, 2018 , 2017 ). Characteristic features of ALSP include enlarged ventricles, cerebral atrophy, periventricular calcifications and thinning of the corpus callosum ( Konno et al, 2018 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Actually, using the NeuroChip, Blauwendraat et al (2019) analyzed rare variants of damaging mutations in 1243 autopsy-confirmed neurodegenerative cases that were diagnosed as AD, FTD or ALS in the Johns Hopkins Brain Resource Center, and identified 2 cases with a pathogenic CSF1R mutation (p.G589E, and p.M755T or M766T) and 1 case with a likely pathogenic CSF1R mutation (p.L868P). Thus, there are complex genotype-phenotype associated with ALSP (Guo and Ikegawa, 2021). Nonetheless, the number of ALSP patients confirmed by genetic diagnosis of CSF1R has been increasing in various populations.…”
Section: Csf1r In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Over the past 20 years, several unrelated families presenting with inherited adult-onset leukodystrophy and pathological neuroaxonal spheroids and pigmented glia have been reported ( Köhler et al, 2018 ). These conditions have been known by a series of names ranging from the initial terms POLD and HDLS to the more recent term adult-onset leukoencephalopathy with axonal spheroids and pigmented glia (ALSP) ( Konno et al, 2018a ; Guo and Ikegawa, 2021 ).…”
Section: Introductionmentioning
confidence: 99%